"Vida Universitária": política, esportes e festas. Uma análise antropológica da sociabilidade estudantil contemporânea - Costa, Carlos Eduardo (2007)
Initially, the objective of this research was to carry out an ethnography of the “tournaments universities”, events that bring together students from different institutions of higher education around parties and sports competitions. The expansion of the empirical scope, however, came in the sense of showing that the tournaments, for in addition to the sporting enjoyment and sociability they instill, they are deeply intertwined with a university ethos with developments in various spheres, from the domestic one, and the analysis of the republics attests to this fact, even the public universe of clashes typical of student politics. The research intends to renew, in a certain sense, the works on the manifestations students insofar as they link them to a broader university symbolic system, revealing a dynamic of its own where the ethos of the game, the party and the sport are not outside the political decision-making. It is, in fact, a system that does not end in the object “university sport” itself. In the analysis of “republics”, for example, the notion of house proposed by Lévi-Strauss for kinship studies proved to be quite fruitful, since the affinity regime defined in these student houses, as revealed by the native categories operationalized there, such as friendship, arrival, “brother”, intertwine and dialogue with regimes of affective, ideological affinity. Without an ethnography of these practices that permeate this intense sociability, visible in the games and tournaments, but which is also important in the everyday sphere, in the domestic, returning to the public sphere from the student claims movements, it is not would understand the more universal training process of these young university students in Brazil.